Effect of Correcting Peripheral Refractive Errors on Retinal Sensitivity in Younger and Older Healthy Adults. Issue 4 (27th April 2023) - João, Catarina A. R.; Scanferla, Lorenzo; Alarcon, Aixa; van der Mooren, Marrie; Jansonius, Nomdo M.
Abstract : SIGNIFICANCE: Retinal sensitivity decreases with age and age-related eye diseases. Peripheral retinal sensitivity may also be compromised if the refractive correction is not optimized for peripheral vision. PURPOSE: This study aimed to determine the impact of using a peripheral refractive correction on perimetric thresholds and the influence of age and spherical equivalent on this impact. METHODS: We measured, in 10 younger (20 to 30 years) and 10 older (58 to 72 years) healthy subjects, perimetric thresholds for Goldmann size III stimulus in several test locations along the horizontal meridian of the visual field (eccentricity, 0, ±10, and ±25°), with default central refractive correction and with peripheral refractive corrections as measured with a Hartmann-Shack wavefront sensor. We used analysis of variance to determine the effect of age and spherical equivalent (between-subject variables) and eccentricity and correction method (central vs. eccentricity specific; within-subject variables) on retinal sensitivity. RESULTS: Retinal sensitivity was higher if the eyes were optimally corrected for the concerning test location ( P = .008), and the effect of this peripheral correction differed between the younger and older subjects (interaction term between group and correction method: P = .02), primarily because of more myopia in the younger group ( P = .003). The average improvement by applying peripheral corrections was 1.4 dB in the older subjects and 0.3 dB in the younger subjects. CONCLUSIONS: Peripheral optical correction has a variable impact on retinal sensitivity, and therefore, assessment of retinal sensitivity may be more accurate if peripheral defocus and astigmatism are corrected.